2012
DOI: 10.1103/physrevd.85.124024
|View full text |Cite
|
Sign up to set email alerts
|

Hairy charged Gauss-Bonnet solitons and black holes

Abstract: We study the stability of (4+1)-dimensional charged Gauss-Bonnet black holes and solitons. We observe an instability related to the condensation of a scalar field and construct explicit "hairy" black hole and soliton solutions of the full system of coupled field equations. We investigate the cases of a massless scalar field as well as that of a tachyonic scalar field. The solitons with scalar hair exist for a particular range of the charge and the gauge coupling. This range is such that for intermediate values… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…Qualitatively similar results exist when describing insulator/superfluid phase transitions with non-vanishing superfluid velocity [29]. Charged solitons in global AdS have also recently been studied in 4 dimensions [34] as well as in 5 dimensions [35,36].…”
Section: Introductionsupporting
confidence: 58%
“…Qualitatively similar results exist when describing insulator/superfluid phase transitions with non-vanishing superfluid velocity [29]. Charged solitons in global AdS have also recently been studied in 4 dimensions [34] as well as in 5 dimensions [35,36].…”
Section: Introductionsupporting
confidence: 58%
“…This has already been considered in [34]. Here we point out further important details in the pattern of solutions.…”
Section: Static Black Holesmentioning
confidence: 66%
“…It was pointed out that the solutions tend to their planar counterparts for large charges since in that case the solutions can become comparable in size to the AdS radius. The influence of the Gauss-Bonnet corrections on the instability of these solutions has been discussed in [34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The late-time evolution of a self-interacting scalar field for a dilatonic black hole has also been analyzed [142]. It may be noted that the scalar hair for charged Gauss-Bonnet black holes have been studied [143]. It has been demonstrated that the solitons with scalar hair exist for a particular range of the charge and the gauge coupling.…”
Section: Phase Transition Points Through Heat Capacitymentioning
confidence: 99%